2005
DOI: 10.1149/1.1938067
|View full text |Cite
|
Sign up to set email alerts
|

Two-Phase Transport in Polymer Electrolyte Fuel Cells with Bilayer Cathode Gas Diffusion Media

Abstract: A two-phase, full cell model based on the multiphase mixture ͑M 2 ͒ framework is developed to analyze the two-phase transport in polymer electrolyte fuel cells with bilayer cathode gas diffusion media ͑GDM͒, consisting of a coarse gas diffusion layer ͑GDL͒ with an average pore size around 10-30 m and a microporous layer ͑MPL͒ with an average pore size ranging from 0.1 to 1 m. Effects of the relevant properties of the MPL on liquid water transport are examined, including average pore size, wettability, thicknes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
176
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 245 publications
(185 citation statements)
references
References 34 publications
(42 reference statements)
4
176
0
Order By: Relevance
“…For practical uses of PEFC, water flooding at high current density conditions is one of the major issues to be improved, because flooding deteriorates efficiency and maximum power output due to limiting the supply of reactants to the reaction area by the water accumulated in the cell. It is generally known that a micro-porous layer (MPL) contributes to better water removal from the cathode catalyst layer (CL) and to improvements in the cell performance [1][2][3][4]. The MPL introduces a -2 -fine carbon layer between the CL and gas diffusion layer (GDL), and has smaller pore sizes than the GDL.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For practical uses of PEFC, water flooding at high current density conditions is one of the major issues to be improved, because flooding deteriorates efficiency and maximum power output due to limiting the supply of reactants to the reaction area by the water accumulated in the cell. It is generally known that a micro-porous layer (MPL) contributes to better water removal from the cathode catalyst layer (CL) and to improvements in the cell performance [1][2][3][4]. The MPL introduces a -2 -fine carbon layer between the CL and gas diffusion layer (GDL), and has smaller pore sizes than the GDL.…”
Section: Introductionmentioning
confidence: 99%
“…Early computational studies reported that the MPL improves water removal from the cathode GDL by increasing the hydraulic pressure differential across the membrane [1], and that the MPL acts like a valve that pushes water away from the cathode and towards the anode through the membrane [2]. Gostick et al estimated the water saturation and capillary pressure for GDLs with and without an MPL from the measured conditions of the liquid water breakthrough at the porous layers, and suggested that the efficacy of the MPL is due to finite-size effects related to invasion percolation in thin GDLs where liquid water percolation through the MPL results in limited access of water to the GDL inlet face [5].…”
Section: Introductionmentioning
confidence: 99%
“…Past studies have shown that the properties of both the GDL substrate and MPL play a significant role in water balance and performance of proton exchange membrane (PEM) fuel cells [1][2][3][4][5][6]. In these studies of GDLs, the impact of GDL materials and design on PEM fuel cell performance losses, rather than durability, has been the focal point.…”
Section: Introductionmentioning
confidence: 99%
“…The earlier theoretical 4 models hypothesized that the water produced in the cathode condensed in the CL first, and it was then driven into the MPL by a capillary pressure gradient [23]. Since the MPL was assumed to be more hydrophobic than the CL, these models predicted that with an increase in MPL thickness, the water would gradually flood the part of MPL adjacent the CL.…”
Section: Introductionmentioning
confidence: 99%